2018
DOI: 10.1111/appy.12310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for problematic Internet use among rural adolescents in Korea

Abstract: The findings indicate a need to develop preventive interventions for PIU among rural adolescents in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
2
28
2
8
Order By: Relevance
“…As previously mentioned, program activities of this CST version were more engaging for school‐aged children than for adolescents despite our efforts to have program interactive components relevant to youth with type 1 diabetes of different ages. Adolescents with type 1 diabetes may benefit more from a program specific to their diabetes‐related challenges and may also prefer a program that incorporates technology or social media . More formative research involving adolescents with type 1 diabetes and parents in China is needed.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, program activities of this CST version were more engaging for school‐aged children than for adolescents despite our efforts to have program interactive components relevant to youth with type 1 diabetes of different ages. Adolescents with type 1 diabetes may benefit more from a program specific to their diabetes‐related challenges and may also prefer a program that incorporates technology or social media . More formative research involving adolescents with type 1 diabetes and parents in China is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older age can also be a risk factor for IGD, as compared to younger age among adolescents 14. Activity factors may consist of academic achievement, activity in leisure time, and social activity 1516. In a survey of US students in 27 universities, sadness and depressive mood, boredom, and stress could be associated with intensive internet use 16.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the failure of academic achievement or exercise, failure to engage in face-to-face social activities, negative affective states, and concentration difficulties could also induce excessive internet use 16. In a survey with 1,168 Korean adolescents regarding problematic internet use, Lee et al15 reported that academic stress was significantly associated with problematic internet use. In a survey of 509 adolescents aged 10–18 years, social networking site (SNS) addiction and IGD could augment each other and simultaneously contribute to aggravating clinical symptoms 10.…”
Section: Introductionmentioning
confidence: 99%
“…A study found a significant association between IA and depression [25]. In a two-year prospective study, depression was identified as a predictor of IA among women [26].…”
Section: Introductionmentioning
confidence: 99%